Developing a novel alpha‐synuclein positron emission tomography (PET) tracer for the diagnosis of synucleinopathies: Neuroimaging: Other neurodegenerative disorders. (7th December 2020) - Capotosti, Francesca; Vokali, Efthymia; Molette, Jerome; Tsika, Elpida; Ravache, Myriam; Juergens, Tanja; Melo dos Santos, Antonio; Darmency, Vincent; Piorkowska, Kasia; Chauhan, Mayank; Kroth, Heiko; Hliva, Valerie; et al.
Abstract: Background: The progressive accumulation of aggregated alpha‐synuclein (a‐syn) in the form of Lewy bodies and neurites is the hallmark of e.g. Parkinson's disease (PD). Due to the low density of a‐syn pathology and the frequency of co‐existing proteinopathies in PD (e.g., beta‐amyloid, tau), an a‐syn PET tracer must display high binding affinity and selectivity to the target, as well as minimal background. Method: [ 18 F]‐ACI‐Cpd‐AE was evaluated in a first‐in‐human (FiH) study. [ 18 F]‐ACI‐Cpd‐AE dynamic PET imaging was conducted over 90 min in five PD subjects (four idiopathic PD, 68.7 years and MDS‐UPDRS III 'off' score 43.3, and one with SNCA duplication, 49 years and MDS‐UPDRS III 'off' score 52) and five healthy volunteers (HV, 58.4 years). Specific retention of [ 18 F]‐ACI‐Cpd‐AE was evaluated by calculating the distribution volume ratio (DVR) from kinetic analysis with an arterial input function and the standardized uptake value ratios (SUVr) from static analysis, using the middle frontal cortex as reference region. In parallel to the FiH evaluation of [ 18 F]‐ACI‐Cpd‐AE, a thorough medicinal chemistry lead to the design of new promising compounds and the throughput of the screening assays was improved. Result: In the FiH study, [ 18 F]‐ACI‐Cpd‐AE displayed fast brain uptake, very low non‐specific retention, rapid metabolism and high free fraction. In this small cohort, no significant evidence of cross‐sectional difference between healthy controls and PD subjects was observed. Averaged across target regions the SUVr (30‐90min) range was 1.15‐1.22 in PD subjects and 1.14‐1.28 in HV. Specifically, in left substantia nigra, mean SUVr was 1.32±0.15 in PD and 1.19±0.18 in HV. Based on these clinical data, a new chemical series has been identified to retain affinity and selectivity while improving target occupancy. Conclusion: In house medicinal chemistry efforts led to the discovery of ACI‐Cpd‐AE, a potential a‐syn PET tracer that binds selectively and with high affinity to a‐syn aggregates. In the FiH study, ACI‐Cpd‐AE demonstrated fast brain uptake and low non‐specific retention. Further analyses of the FiH data and evaluation in patients with expected higher levels of pathological brain a‐syn aggregates will be performed. In parallel, compounds with improved binding properties have been identified and optimized for further development.